FORMULASI PIDANA PENUTUPAN KORPORASI ATAS DELIK LINGKUNGAN HIDUP - Shofi Munawwir Effendi; I Gede Widhiana Suarda; Fiska Maulidian Nugroho (Faculty of Law, Parahyangan Catholic University, 2023)
Corporations’ important and strategic role is indispensable to the development of national economy. Even so, economic development should not be used to serve corporation as justification to sacrifice the environment and wellbeing of the society in order to gain maximum profit. Efforts to develop the mechanism of corporate liability for environmental offenses have been continuously done through the Environment Law issued from 1997 to 2009 and regulations in the Job Creation Law. However, the formulation of responsibility for environmental offenses is still relatively weak, coupled with the absence of a provision for when an environmental offense is committed by a corporation, and the inadequate arrangements for executing punishment for corporations. Through statutory and conceptual approaches, this study seeks to formulate criminal formulations that can be applied to corporations for environmental offenses. In this case, the research is focusing on the additional penalty of corporation dissolution which is seen as the ultimate punishment for corporate law subjects. The existence of dissolution as punishment might serve as an answer to other problems within the realms of environmental law enforcement. This study aims to present provisions of criminal penalties against corporations that pollute and/or damage the environment through editorial norms construction.